Madagascar 2024 - Andrianarisoa, Nandih; Bindloss, Joseph; Drew, Keith (Travel writer); Eveleigh, Mark; Ham, Anthony (Lonely Planet guidebooks., 2023)
Lonely Planet's Madagascar is our most comprehensive guide that extensively covers all the country has to offer, with recommendations for both popular and lesser-known experiences. Spot chameleons and lemurs in national parks, haggle like a local in Antananarivo, and snorkel incredible coral reefs; all with your trusted travel companion.